Influence of Compensation and Workloadon On Employee Job Satisfaction In The Marketing Departement of PT. Fajar Surya Wisesa Tbk, Cikarang - Hernawati, Maya; Hasiholan, Darwin; Setyanto, Eddy (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
The purpose of this study was to determine the effect of "Compensation" and "Workload" on Employee Job Satisfaction in the Marketing Department of PT. Fajar Surya Wisesa Tbk, Cikarang. This study uses a quantitative approach and data collection methods by distributing questionnaires to 46 respondents from employees with positions from foreman to group leader in the Marketing Department of PT. Fajar Surya Wisesa Tbk, Cikarang. Data processing was carried out using SPSS version 25 and analyzed using multiple regression methods. The results of the study indicate that the Compensation variable has a significant positive effect on Employee Job Satisfaction, the Workload variable has a significant negative effect on Employee Job Satisfaction, and Compensation and Workload simultaneously have a significant effect on Employee Job Satisfaction. The value of the coefficient of determination (R2) is 63.4%, this indicates that employee job satisfaction is influenced by 63.4% by compensation and workload while the remaining 36.6% is influenced by other variables outside this study.